Fifteen Years of Inequality in Latin America : How Have Labor Markets Helped? - Azevedo, João Pedro (World Bank, Washington, DC, 2013)
Household income inequality has declined in Latin America in the past decades, contributing significantly to poverty reduction in the region. Although available evidence shows that changes in the labor income are among the main factors behind these inequality trends, few studies have analyzed more closely the labor market dynamics that have led to a decline in total income inequality in some countries, but also to an increase in others. Using household survey data for a sample of 15 countries in Latin America from 1995 to 2010, this paper uses an extension of the Juhn-Murphy-Pierce methodology to decompose changes in labor income inequality (hourly wages) into a quantity effect (capturing changes in the distribution of workers' skills), price effect (reflecting returns to skills), and unobservables effect (other components, within skill groups, affecting labor income). The results show that falling returns to skills for both education and experience is, on average, driving the decline in labor income inequality in Latin America. The quantity effect, in turn, has contributed little to inequality reduction, mostly attributable to a larger dispersion in years of experience, possibly linked to the region's demographic transition and to significant increases in female labor force participation. Additional findings show that wage inequality, still high in the region, is coupled with inequality in terms of hours worked. The paper complements the existing literature by presenting separate results for males and females, as well as formal and informal sector workers as an attempt to control for secular shifts in these characteristics.